Peran Vital Instagram dalam Mitigasi Krisis Kepercayaan Label Halal UMKM - Pramadhanti, Nurul Fara; Ayuningtyas, Fitria (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The halal label is an important factor in purchasing decisions. Communication crises related to halal labeling, which can affect consumer trust, often appear on social media. One real example is the case of Ayam Goreng Widuran Solo, which in 2024, was involved in a controversy after it was revealed that their products used non-halal ingredients, causing confusion and concern among Muslim consumers. This case quickly went viral on social media, affecting the reputation of this long-established restaurant and triggering a significant decline in sales and customer trust. Therefore, a responsive and transparent crisis communication strategy is needed to overcome the negative impact and restore reputation. This study uses a qualitative method that analyzes how UMKM, especially Ayam Goreng Widuran Solo, optimize social media as a crisis communication tool in dealing with the issue of halal labeling. This study combines crisis communication studies with the use of digital platforms, identifying best practices and challenges faced by UMKM in responding to reputation crises in the digital era. The results of the study indicate the importance of a deep understanding of social media algorithms that can influence public perception, as well as the organization's ability to manage communications with timely and accurate responses.